Persepsi Siswa Terhadap Pemanfaatan Gamifikasi Quizizz dalam Pembelajaran di MAN 5 Agam - Dedi Efendi; Zulfani Sesmiarni (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2022)
This study aims to demonstrate how students view the use of Quizizz gamification in the classroom at MAN 5 Agam. The population and respondents of the study were 180 students of MAN 5 Agam from grades 10, 11, and 12 in the 2022â€“2023 academic year. There were 67 respondents that provided questionnaire responses via Google Forms. A Likert scale was used for the analysis of the data. The Google Forms tool was used to distribute online questionnaires to students through the Whatsapp group, which provided the data for the whole research. The findings revealed that most students believed using Quizizz to complete assigned tasks before in-person instruction in class had a positive effect on learning activities. Students believe Quizizz to be a user-friendly tool that makes learning more enjoyable, improves content mastery, and boosts students'Â enthusiasm and engagement in their studies. However, according to students, there are several restrictions and issues in utilizing Quizizz, such as time constraints and internet connection issues.